Governing Road Safety In Urban South Asia: Public Perceptions And Policy Strategies For Animal–Vehicle Collisions In Lahore, Pakistan - *Meharunisa Butt; Ar. Fahad Khan; Ar. Dr. Omer Shujat Bhatti; Ar. Kabeer Ud Din Naseer (Policy Journal of Social Science Review, 2026)
Animal-vehicle collisions (AVCs) represent a significant yet understudied challenge in rapidly urbanizing cities of the Global South, where free-roaming domestic animals compound traffic safety risks. While extensive research exists on wildlife-vehicle collisions in developed nations, little attention has been given to urban AVC dynamics in South Asian contexts. Therefore, this study aims to explore public perceptions of AVCs and evaluate preferred prevention strategies in Lahore, Pakistan, where free-roaming livestock and stray animals significantly impact traffic safety. Using a structured questionnaire survey administered to 575 respondents, the research indicate that vehicle speed emerges as the most critical factor, particularly among respondents aged 31-40 years, while poor lighting and lack of signage are widely recognized as contributing elements to AVCs. Female participants indicated stronger support for regulatory measures such as speed enforcement, and male respondents supported infrastructural solutions, i.e., fencing to mitigate AVCs. To reduce AVCs, educational attainment significantly influences preferences, as highly educated respondents prioritize awareness campaigns while those with primary education emphasize practical roadside maintenance. These findings provide empirical evidence to guide the development of context-sensitive prevention strategies in South Asian cities, suggesting the need for integrated approaches that combine infrastructure improvements, public education initiatives, and policy reforms. Keywords: Animal-Vehicle Collisions (AVCs), Traffic Safety, Free-Roaming Animals, Urban Transportation, Road Infrastructure.